Hepatotoxicity after Sevoflurane Exposure in a Patient with Chronic Hepatitis C - Nickul N Shah; Nina Ballone; Raul Zamora; Peter DeVito; Samuel Wilson (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2015)
Sevoflurane is considered a safe inhaled anesthetic of choice in patients with liver disease. Compared to other halogenated inhaled anesthetics, Sevoflurane is reported to lessen the severity of decreased hepatic blood flow and undergoes a different mechanism of hepatic metabolism. In patients with preexisting liver disease, there is potential for low-flow Sevoflurane to induce acute liver damage through other mechanisms. Limited data exists to guide clinical decision-making when quantifying the severity of cirrhosis in patients with hepatitis C and its relationship to anesthesia choice. Previous studies have found that exposure to general anesthesia during abdominal surgery may increase the risk of hepatorenal failure. This study has raised a concern that anesthetics may interfere with various hepatic functions secondary to viral infection. The generation of abnormal liver enzymes and hypercoagulation has provided further exploration for such toxicity.